Characterization and Application of Molten Slag as Catalyst in Pyrolysis of Waste Cooking Oil - Salmiaton Ali; Raja Mohamad Hafriz Raja Shahruzzaman; Intesar Razaq Hussien; Rozita Omer; Faten Hameed Kamil (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Chemical and physical analysis was performed to identify the molten slag composition and its ability to be used as alternative catalyst in pyrolysis of waste cooking oil. The implementation such type of catalytic material could be useful in reducing the process cost. To increase the efficiency (increase the active site) of molten slag, it was modified by acid washing that resulted in an increase in the acidity from 159 to 1224 µmol/g. The results showed that the yield of bio-fuel was increased and the product selective to n-C15 upon the modification of molten slag by acid treatment. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).